2022
DOI: 10.1159/000526234
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Outcomes of Peritoneal Dialysis Patients in the Post-COVID-19 Period: A National Multicenter Case-Control Study from Turkey

Abstract: <b><i>Introduction:</i></b> There are not enough data on the post-CO­VID-19 period for peritoneal dialysis (PD) patients affected from COVID-19. We aimed to compare the clinical and laboratory data of PD patients after COVID-19 with a control PD group. <b><i>Methods:</i></b> This study, supported by the Turkish Society of Nephrology, is a national, multicenter retrospective case-control study involving adult PD patients with confirmed COVID-19, using data collect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
2
0
Order By: Relevance
“…Consistent with our research findings, patients with PD with high iron levels have a four-fold higher risk of all-cause cardiovascular death [22]. The effect of the COVID-19 pandemic on patients with PD is still being debated, and certain authors argue that COVID-19 has no effect on the survival of patients with PD [23].…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our research findings, patients with PD with high iron levels have a four-fold higher risk of all-cause cardiovascular death [22]. The effect of the COVID-19 pandemic on patients with PD is still being debated, and certain authors argue that COVID-19 has no effect on the survival of patients with PD [23].…”
Section: Discussionsupporting
confidence: 87%
“…Data from an observational study in Turkey reported that the mortality rate was high (46.2%) in PD-hospitalized patients with COVID-19 [127]. In addition, according to the European Renal Association database, COVID-19 PD patients had a higher mortality risk than HD patients, even after accounting for patient characteristics and disease severity [15].…”
Section: Covid-19 In Dialysis Patientsmentioning
confidence: 99%
“…A Turkish study of 113 PD patients in 2021 reported that COVID-19 had no significant association with PD characteristics and baseline laboratory data. 9 Another study showed a difference in vaccination rate, sex predominance and primary kidney disease between the COVID-19 and non-COVID-19 groups in 127 Tunisian PD patients from 2019 to 2021. 10 A cohort study involving 1,487 PD patients between August 2021 and July 2022 in Thailand showed that the predictors of COVID-19-related death in PD patients were similar to those in haemodialysis patients, including vaccine, corticosteroid therapy, delta variant and need for respiratory support.…”
Section: Introductionmentioning
confidence: 99%